Islamization of Knowledge in Historical Perspective - Ahmad Nabil Amir (Tarikhuna: Journal of History and History Education, 2023)
The paper discusses the epistemological framework of Islamization of knowledge, in light of its contextual and philosophical ideals and discursive history and current debates of Islamization of contemporary knowledge. It looks into the role of its major proponents and institutions in articulating the ideas of IOK and the principle of tawhid in late 1970-80s and its impact in spearheading the movement for intellectual renewal and reassertion of tawhidic and ethical consciousness. This was consistently undertaken by IIUM and IIIT in promoting the doctrine of Islamization of human knowledge and assimilation of knowledge and value. The research was qualitative in nature in the form of integrative library research and documentation technique. It conducts comprehensive survey of related primary and secondary sources and analyzed it through inductive and deductive method. The finding shows that the principal ideas of IOK was constructed based on the tawhidic worldview and its epistemological framework while the fundamental issues and concept of Islamization continued to be articulated that addresses its challenge and paradigm and basic methodology and workplan.